2020
DOI: 10.1186/s40463-020-00438-1
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis type 2 initially presenting as a preauricular mass: A case report

Abstract: Neurofibromatosis type 2 (NF2) is a rare genetic disease involving multiple tumors of the central and peripheral nervous systems. Most patients with NF2 have bilateral vestibular schwannomas; nonvestibular schwannomas may also develop. While the majority of patients may present with hearing impairment, tinnitus, dizziness and balance disorders, some may present with cutaneous manifestations. We describe the case of a 20-year-old man who initially presented with a solitary subcutaneous painless nodule in the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This is compatible with Lan et al, who reported that most NF2 adult patients initially presented with unilateral hearing loss with accompanying or preceding tinnitus. 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is compatible with Lan et al, who reported that most NF2 adult patients initially presented with unilateral hearing loss with accompanying or preceding tinnitus. 7 …”
Section: Discussionmentioning
confidence: 99%
“…This is compatible with Lan et al, who reported that most NF2 adult patients initially presented with unilateral hearing loss with accompanying or preceding tinnitus. 7 The pathophysiology of NF2 hearing loss is not fully understood and may be attributable to several complex factors including; direct mechanical compression of the adjacent neurovascular structures, tumour secreting factors that cause a loss of hair cells, and elevated perilymphatic protein level that induce cochlear dysfunction. 6 A study by Asthagiri et al indicated that elevated intralabyrinthine perilymphatic proteins may underlie hearing loss, and labyrinthine high signal intensity on MRI in normal hearing ears may serve as an imaging biomarker for developing hearing loss.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%
“…The most common cutaneous abnormalities in NF2 are schwannomas, 4,5 although neurofibromas and mixed tumors have occasionally been identified. 6–8 While neurofibromas (and cafe au lait spots) may occur in NF2 they do so in lesser frequency than in NF1.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, even though these tumors are benign, they are associated with significant morbidity and the potential for early mortality [ 7 ]. In the case of Lan WC et al., NF2 patients may present with an isolated, solitary cutaneous schwannoma with no other associated clinical findings [ 8 ]. However, further assessment is warranted in young patients presenting with a peripheral schwannoma with no other clinical findings [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of Lan WC et al., NF2 patients may present with an isolated, solitary cutaneous schwannoma with no other associated clinical findings [ 8 ]. However, further assessment is warranted in young patients presenting with a peripheral schwannoma with no other clinical findings [ 8 ]. Subsequently, Baser et al.…”
Section: Discussionmentioning
confidence: 99%